Healthcare-associated Staphylococcus aureus bloodstream infection: length of stay, attributable mortality, and additional direct costs - Mariusa Gomes Borges Primo; Adriana Oliveira Guilarde; Celina M. Turchi Martelli; Lindon Johnson de Abreu Batista; Marília Dalva Turchi (Brazilian Journal of Infectious Diseases, 2012)
This study aimed to determine the excess length of stay, extra expenditures, and attributable mortality to healthcare-associated S. aureus bloodstream infection (BSI) at a teaching hospital in central Brazil. The study design was a matched (1:1) case-control. Cases were defined as patients > 13 years old, with a healthcare-associated S. aureus BSI. Controls included patients without an S. aureus BSI, who were matched to cases by gender, age (± 7 years), morbidity, and underlying disease. Data were collected from medical records and from the Brazilian National Hospital Information System (Sistema de Informações Hospitalares do Sistema Único de Saúde - SIH/SUS). A Wilcoxon rank sum test was performed to compare length of stay and costs between cases and controls. Differences in mortality between cases and controls were compared using McNemar's tests. The Mantel-Haenzel stratified analysis was performed to compare invasive device utilization. Data analyses were conducted using Epi Info 6.0 and Statistical Package for Social Sciences (SPSS 13.0). 84 case-control pairs matched by gender, age, admission period, morbidity, and underlying disease were analyzed. The mean lengths of hospital stay were 48.3 and 16.2 days for cases and controls, respectively (p < 0.01), yielding an excess hospital stay among cases of 32.1 days. the excess mortality among cases compared to controls that was attributable to s. aureus bloodstream infection was 45.2%. Cases had a higher risk of dying compared to controls (OR 7.3, 95% CI 3.1-21.1). Overall costs of hospitalization (SIH/SUS) reached US$ 123,065 for cases versus US$ 40,247 for controls (p < 0.01). the cost of antimicrobial therapy was 6.7 fold higher for cases compared to controls. healthcare-associated s. aureus BSI was associated with statistically significant increases in length of hospitalization, attributable mortality, and economic burden. Implementation of measures to minimize the risk of healthcare-associated bacterial infections is essential.